A Pilot SMART for Developing an Adaptive Treatment Strategy for Adolescent Depression. Issue 4 (3rd July 2016) - Gunlicks-Stoessel, Meredith; Mufson, Laura; Westervelt, Ana; Almirall, Daniel; Murphy, Susan
Abstract : This pilot study was conducted to assess the feasibility and acceptability of 4 adaptive treatment strategies (ATSs) for adolescent depression to plan for a subsequent full-scale clinical trial. The ATSs aim to address 2 questions that arise when personalizing treatment: (a) For adolescents treated with Interpersonal Psychotherapy for depressed adolescents (IPT-A; Mufson et al., 2004 ), at what time point should therapists make the determination that the adolescent is not likely to respond if the initial treatment plan is continued (week 4 or week 8)? (b) For adolescents who are judged to need their treatment augmented, should the therapist increase the number of IPT-A sessions or add pharmacotherapy (fluoxetine)? A 16-week pilot sequential multiple assignment randomized trial (SMART) was conducted with 32 adolescents ( M age = 14.9) who had a diagnosis of major depressive disorder, dysthymic disorder, or depressive disorder not otherwise specified. Adolescents were primarily female (75%) and Caucasian (84.4%). Data regarding the feasibility and acceptability of the study and treatment procedures and treatment response rates were collected. Week 4 was the more feasible and acceptable decision point for assessing need for a change to treatment. Adolescents, parents, and therapists reported a range of attitudes about medication and more intensive therapy as treatment options. Results from the pilot study have yielded additional research questions for the full-scale SMART and will improve our ability to successfully conduct the trial.